2018
DOI: 10.1029/2018jd029210
|View full text |Cite
|
Sign up to set email alerts
|

The Flux and Emission of Dimethylsulfide From the Great Barrier Reef Region and Potential Influence on the Climate of NE Australia

Abstract: Concentrations of dimethylsulfoniopropionate (DMSP), dimethylsulfide (DMS), and DMS flux are reported for the Great Barrier Reef (GBR), Great Barrier Reef Lagoon (GBRL), and Coral Sea. Generally higher concentrations of dimethylsulfoniopropionate and DMS occurred in coral reef waters, compared with GBRL concentrations. DMS flux from GBR coral reefs in summer ranged from nondetectable to 153 μmol m−2 d−1 (mean 6.4), while winter fluxes ranged from 0.02 to 15 μmol m−2 d−1 (mean 2.4). No significant seasonal diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 77 publications
(225 reference statements)
9
39
0
Order By: Relevance
“…The results presented in this analysis support existing findings that corals in the GBR are a significant source of DMS a (Fischer & Jones, 2012; Haydon et al, 2018; Jones et al, 2018; Raina et al, 2013; Swan et al, 2016; Swan, Jones, Deschaseaux, & Eyre, 2017). Ongoing ocean warming and coral bleaching may therefore lead to a change in DMS emissions from the GBR.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results presented in this analysis support existing findings that corals in the GBR are a significant source of DMS a (Fischer & Jones, 2012; Haydon et al, 2018; Jones et al, 2018; Raina et al, 2013; Swan et al, 2016; Swan, Jones, Deschaseaux, & Eyre, 2017). Ongoing ocean warming and coral bleaching may therefore lead to a change in DMS emissions from the GBR.…”
Section: Discussionsupporting
confidence: 87%
“…The coral reef flat often becomes aerially exposed during low tide and DMS may be directly transferred from the coral reef to the MBL (Hopkins et al, 2016; Swan, Jones, Deschaseaux, & Eyre, 2017). DMS emissions also increase on rising tides when DMS in coral mucous dissolves and accumulates in tidal slack waters (Hopkins et al, 2016; Jones et al, 2007; Jones et al, 2018; Swan, Jones, Deschaseaux, & Eyre, 2017). The highest spike occurred during the evening low tide of 25 July and Swan, Jones, Deschaseaux, and Eyre (2017) concluded that rainfall (hyposalinity) and rapid temperature change stressed the exposed corals.…”
Section: Discussionmentioning
confidence: 99%
“…As Acropora are the dominant genus throughout the Indo-Pacific and are amongst the strongest producers of DMS/P, it was estimated that corals in the GBR release 3 -11 mmol S m -2 day -1 . According to this estimate the GBR releases 0.01 -0.04 Tg S yr -1 , consistent with the estimate provided by Jones et al (2018). Assuming that DMS flux is constant across coral reefs and lagoon waters, tropical coral reefs (~600,000 km 2 ) emit 0.02 -0.08 Tg S yr -1 .…”
Section: The Claw Hypothesissupporting
confidence: 87%
“…km 2 ) are estimated to emit 0.02 Tg S year -1 (Jones et al, 2018). It is noted that coral cover in the GBR is ~20,000 km 2 and consequently, DMS flux from the surrounding lagoon was far higher than estimates from the coral reef.…”
Section: The Claw Hypothesismentioning
confidence: 96%
“…However, high LLC cover significantly reduced the amount of surface solar radiation at coral reefs in the nearby So-ciety Islands, where bleaching did not occur (Mumby et al, 2001b). Similarly, high SST (> 31 • C) in 1994 caused coral bleaching at Nelly Bay (Magnetic Island) in the central GBR (Jones et al, 1997); however, no bleaching was observed ∼ 60 km away at Pioneer Bay (Orpheus Island; Jones et al, 2007). Jones et al (2017) examined DMS a before, during and after this bleaching event at both locations.…”
Section: Influence On Low-level Clouds Sea Surface Temperature and Smentioning
confidence: 99%